Development of ZnO-NPs reinforced chitosan nanofiber mats with improved antibacterial and biocompatibility properties - Parva Safari; Eshagh Zakipour Rahimabadi; Mohammad Reza Vaezi; Aliasghar Behnamghader; Reza Tahergorabi (Scientific Reports)
Abstract This paper studied the possibility of fabricating a nano-composite based on chitosan incorporated with ZnO-NPs as a promising textile for wound dressing purposes. The nanofiber mat was obtained from dispersions of ZnO-NPs in chitosan-based solution blended with PVA (Cs/PVA/ZnO-NPs scaffold). The extracted chitosan was characterized using FTIR, FE-SEM, XRD, and TGA analysis. The electrospinning optimization process was successfully done for Cs and PVA mixture and a good combination of polymers, solvent, and the ratios developed through an optimization process (10wt.% PVA and 1wt.% CS in AcAcetic 80%). The nanofibers had an average diameter below 200 nm, while the incorporation of ZnO-NPs decreased their average diameter below 150 nm. FTIR, FE-SEM, XRD analysis were used to evaluate the scaffold structure. The FE-SEM analysis proved the smooth and bead-free morphology of the fibers. Elemental analysis of the mat revealed a good distribution of ZnO-NPs along nanofibers. Cell culture studies with L929 mouse fibroblast cells revealed good viability of the cell on the Cs/PVA/ZnO-NPs scaffold. The nanoparticles improved capability of the mat for growth inhibition rate of bacterial colonies and also its wettability. The results also showed the nontoxicity of CS/PVA/ZnO-NPs composite and its considerable potential for future application in wound dressing.